Increased Production of IL-17A-Producing γδ T Cells in the Thymus of Filaggrin-Deficient Mice - Jee, Mia Hamilton; Johansen, Jeanne Duus; Buus, Terkild Brink; Petersen, Trine Hilkjær; Gadsbøll, Anne-Sofie Østergaard; Woetmann, Anders; Ødum, Niels; Thyssen, Jacob Pontoppidan; White, Andrea Jane; Anderson, Graham; Geisler, Carsten; Bonefeld, Charlotte Menné (Frontiers in Immunology, 2018)
Mutations in the filaggrin gene (Flg) are associated with increased systemic levels of Th17 cells and increased IL-17A production following antigen exposure in both humans and mice. In addition to Th17 cells, γδ T cells can produce IL-17A. The differentiation of γδ T cells to either IFNγ- or IL-17A-producing (γδT17) cells is mainly determined in the thymus. Interestingly, it has been reported that filaggrin is expressed in the Hassall bodies in the human thymic medulla. However, whether filaggrin affects γδ T cell development is not known. Here, we show that filaggrin-deficient flaky tail (ft/ft) mice have an increased number of γδT17 cells in the spleen, epidermis and thymus compared to wild type (WT) mice. We demonstrate that filaggrin is expressed in the mouse thymic medulla and that blocking the egress of cells from the thymus results in accumulation of Vγ2+ γδT17 cells in the thymus of adult ft/ft mice. Finally, we find increased T cell receptor expression levels on γδ T cells, and increased levels of IL-6 and IL-23 in the thymus of ft/ft mice. These findings demonstrate that filaggrin is expressed in the mouse thymic medulla and that production of Vγ2+ γδT17 cells is dysregulated in filaggrin-deficient ft/ft mice.